Power Dynamics and Colonial Exploitation: Unveiling Predatory Forces in ‘Rise of the Planet of the Apes' - Silaen, Ayleen Latiesha; Potoboda, Cerin; Marpaung, Chloe Fay (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2023)
This abstract explores the dynamics of power, oppression, and resistance within the context of colonialism and postcolonialism, drawing on Robert J.C. Young's theoretical framework (2005). Analyzing the movie's portrayal of humans' control over apes, the hierarchical relationship between colonizers and colonized becomes evident. The belief in human supremacy over apes is contextualized within discussions of colonial ideologies and racial hierarchies, reflecting a colonial mindset rooted in notions of superiority. The apes' revolt against human captors mirrors historical resistance movements against exploitation and mistreatment. As a result: 1) The apes have been the subjects of experiments and exploited by the men; men keep forcing the apes to cooperate in experiments (Exploitation and Resistance). 2) The apes often get extreme abuse for the sake of the human race (Power Dynamics and Oppression). 3) The men’s superiority towards the apes creates resistance to fight back humans (Colonial Supremacy and Racial Hierarchies). It highlights the apes' vulnerability to human dominance, their determination to resist, and the potential for collective strength. The contrasting loyalty of apes and humans is underscored, shedding light on the dynamics of power and unity in the face of oppression. As Young's definition of colonialism comes to life, the complex interplay between dominance, resistance, and shared fears emerges, providing a thought-provoking perspective on the movie's themes.